Enhancing Schools’ Development Activities on Inclusive Education Through In-service Training Course for School Teams: A Case Study - Kivirand, Tiina; Leijen, Äli; Lepp, Liina (Frontiers in Psychology, 2022)
Most countries face the challenge of reconstructing their education systems to ensure equitable quality education for all children in inclusive settings. This challenge is also relevant in Estonia, the context of this study. A long-term in-service training course for school teams (school leaders, support specialists, and teachers) was developed and implemented in Estonia. The main goal of the training course was to develop attitudes, skills, and knowledge of school staff about the concept and meaning of inclusive education (IE) and the effective implementation through inclusive school development strategies. The aim of the current study was to find out how the in-service training course for school teams influences system-wide changes in the implementation of IE at the school level and what factors affect it. Purposeful sampling (two schools) was used, and the qualitative thematic case study research method was chosen to find answers to the research questions. Data were collected from school policy documents, homework assignments of the training course, semi-structured interviews in the middle and at the end of the training course, open-ended questionnaires at the end of the training course, and researcher diary. The results showed that the in-service training course for school teams enhanced cultural and structural changes at the school level. These changes were influenced by factors such as leadership, collaboration, commitment, and contribution of different parties, system-wide approach, resources, and external expertise. The implications of these findings are discussed further in the paper.